Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Keywords: LGBTQIA2+; amériques; approches et analyses; discipline; fem1000; féminisme décolonial; littérature; mexique; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

Feminism as critique: On the politics of gender - Benhabib, Seyla; Cornell, Drucilla (University of Minnesota Press, 1987)
Il s'agit d'un remarquable recueil d'essais qui rassemble pour la première fois l'œuvre d'un groupe d'écrivain.e.s bien connu dans la tradition marxiste-féministe. Les essais vont de Marx à Foucault et vont au-delà pour offrir de véritables avancées dans la manière dont la vie sociale et politique peut être reconceptualisée à la lumière de la critique féministe
Keywords: 1900-1999; approches et analyses; cycles supérieurs; discipline; fem9000; féminisme marxiste; genre; identités de genre; inégalités; périodes historiques; science politique; science politique et droit; systèmes d'oppression; thématiques

Feminist practice and poststructuralist theory - Weedon, Chris (Blackwell, 1987)
Feminist Practice and Poststructuralist Theory offers a clear and accessible introduction to poststructuralist theory, focusing on questions of language, subjectivity and power.
Section: viii, 187 p
Keywords: 1900-1999; 1980-1989; discipline; europe; fem1000; linguistique; post-structuralisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; théories féministes

Geography of gender in the third world - Momsen, Janet Henshall; Townsend, Janet G. (University of New York Press, 1987)
This pioneering book addresses a key issue in development studies. It follows the influential 'Geography and Gender' as the second collaborative work generated by the Women in Geography Study Groups of the Institute of British Geographers. Its twenty substantive papers explore spatial patterns of gender in Asia, Africa, the caribbean and Latin America. The book's contributors come from Europe, North and South America, India, Sri Lanka, Malaysia, Thailand, Egypt and the Caribbean. 'Geography of Gender in the Third World' analyses the position of women and the societies that ignore and exploit them. it provides both substantial original research and a comprehensive introduction to the geography of gender in low income countries. The book makes a powerful claim for the regional geography of gender.
Keywords: 1900-1999; afrique; amériques; asie; fem1000; genre; premier cycle; périodes historiques; régions géographiques; sud global; thématiques

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discipline; fem1000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

L'émergence d'une culture au féminin - Zavalloni, Marisa (Éditions Saint-Martin, 1987)
Comment définir une culture au féminin ? Quelles formes peut-elle prendre dans les sciences sociales, la littérature, la philosophie et l’art ? Les recherches présentées dans ce recueil, par leur approche analytique, humoristique, caustique, radicale ou poétique, apparaitront comme la poursuite du même idéal, créer une société dans laquelle « les femmes s’appartiennent totalement, non seulement physiquement, mais symboliquement ».
Keywords: 1900-1999; 1980-1989; amériques; droits des femmes*; fem1000; interdisciplinarité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études culturelles

La dialectique de la reproduction - O'Brien, Mary (Les éditions du remue-ménage, 1987)
Dans La dialectique de la reproduction, essai de philosophie féministe, Mary O’Brien montre comment la pensée masculine et les institutions patriarcales ont été édifiées pour contrecarrer l’incertitude de la paternité et pour médiatiser l’exclusion des hommes du travail reproductif.
Keywords: 1900-1999; EDI; approches et analyses; care; corps; discipline; division sexuelle du travail; fem1000; justice reproductive; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; travail du care

La recherche-action : ses fonctions, son fondement et son instrumentalisation - Goyette, Gabriel; Lessard-Hébert, Michelle (Presses de l'Université du Québec, 1987)
Cet ouvrage définit la recherche-action et ses grands principes et aborde ses finalités et fonctions. On y trouve des tableaux récapitulatifs des fondements et grandes étapes associées à ce type de recherche. (résumé équipe ORPCC)
L'ouvrage est disponible en ligne à un prix modique : https://www.puq.ca/catalogue/livres/recherche-action-ses-fonctions-ses-fondements-414.html
Keywords: 1980-1990; amériques; groupes communautaires; groupes de femmes; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; québec; recherche-action; recherches en milieux de pratiques; ressource en ligne; régions géographiques

Maria W. Stewart, America's first Black woman political writer : essays and speeches - Stewart, Maria W. (Indiana University Press., 1987)
En rassemblant et en présentant les œuvres de Stewart, Richardson offre aux lecteurices l'occasion d'étudier les pensées et les paroles de cette influente militante noire, précurseuse de Frederick Douglass et de Sojourner Truth et première noire américaine à donner des conférences pour la défense des droits des femmes, la plaçant dans le contexte du mouvement abolitionniste tourbillonnant.
Keywords: 1800-1899; amériques; antiesclavagisme; approches et analyses; discipline; droits des femmes*; fem1000; femmes* afro-américaines; féminisme noir; histoire; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

Reading black, reading feminist: A critical anthology - Gates, Henry Louis (Meridian Book, 1987)
A unique and comprehensive collection of 26 literary essays that provides real evidence of the rich cultural history of black women in America. Black women’s writing has finally emerged as one of the most dynamic fields of American literature. Here, leading literary critics—both male and female, black and white—look at fiction, nonfiction, poetry, slave narratives, and autobiographies in a totally new way. In essence, they reconstruct a literary history that documents black women as artists, intellectuals, symbol makers, teachers, and survivors. Important writers whose work and lives are explored include Toni Morrison, Gloria Gaynor, Maya Angelou, and Alice Walker, and the fascinating list of essays range from Nellie Y. McKay’s “The Souls of Black Women Folk in the Writings of W. E. B. Du Bois” to Jewelle L Gomez’s very personal tribute to Lorraine Hansberry as a dramatist and crusader for social justice. Henry Louis Gates Jr., the editor of this anthology and a noted authority on African-American literature, has provided a thought-provoking introduction that celebrates the experience of “reading black, reading feminist.” A penetrating look at women’s writing from a unique perspective, this superb collection brings to light the rich heritage of literary creativity among African-American women.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; arts; discipline; fem1000; feminismes noirs; femmes* noires; pratiques féministes; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires

The Concept of ‘Difference’ - Barrett, Michèle (Feminist Review, 1987)
Keywords: cycles supérieurs; discipline; fem9000; ressource en ligne; sciences humaines; sociologie